Seasonal shifts in the soil microbial community responded differently to in situ experimental warming in a natural forest and a plantation. (14th June 2021) - Zhao, Chunzhang; Wang, Yanjie; Zhang, Nannan; Liang, Jin; Li, Dandan; Yin, Chunying; Liu, Qing
Abstract: Climate warming will shift the seasonal variation of the soil microbial community and thereby regulate the soil process dynamics of forest ecosystems. To evaluate the effects of warming on soil microbial community seasonal dynamics, an in situ experiment was conducted in a natural forest and a dragon spruce plantation in the subalpine region of the eastern Tibetan Plateau. Open‐top chambers (OTCs) were used to increase the mean soil temperature by 0.54 and 0.58°C for the natural forest and plantation, respectively. Our results showed that the initial levels of soil carbon and nitrogen were much higher in the natural forest than in the plantation. Compared to no‐warming, the annual average soil carbon and nitrogen contents increased by 14% and 16% in the natural forest, but decreased by 7 and 6% in the plantation after 4 years of OTC warming, respectively. Conversely, warming caused a significant reduction in the annual average microbial biomass by approximately 50% in the natural forest but enhanced this parameter by approximately 30% in the plantation. Warming further enlarged the differences in seasonal variation in microbial community composition between the two forests. The seasonal variation in microbial community‐level substrate utilization also responded differently to warming in the two forest types. These opposite responses of the soil microbial community and soil properties to warming will further magnify the differences in soil conditions between the two forest types under future climate warming. Highlights: Soil microbial biomass is reduced by warming in the natural forest but increased in the plantation. Seasonal shifts of microbial community respond differently to warming in the two forests. Soil initial properties likely affect responses of microbial community to warming. Warming will enlarge the differences between the two forests.